Highly Efficient Generation of Pigs Harboring a Partial Deletion of the CD163 SRCR5 Domain, Which Are Fully Resistant to Porcine Reproductive and Respiratory Syndrome Virus 2 Infection - Guo, Chunhe; Wang, Min; Zhu, Zhenbang; He, Sheng; Liu, Hongbo; Liu, Xiaofeng; Shi, Xuan; Tang, Tao; Yu, Piao; Zeng, Jianhua; Yang, Linfang; Cao, Yongchang; et al. (Frontiers in Immunology, 2019)
Porcine reproductive and respiratory syndrome virus (PRRSV) 1 and 2 differ in their recognition of CD163. Substitution of porcine CD163 SRCR5 domain with a human CD163-like SRCR8 confers resistance to PRRSV 1 but not PRRSV 2. The deletion of CD163 SRCR5 has been shown to confer resistance to PRRSV 1 in vivo and both PRRSV 1 and 2 in vitro. However, the anti-PRRSV 2 activity of modifying the CD163 SRCR5 domain has not yet been reported. Here, we describe the highly efficient generation of two pig breeds (Liang Guang Small Spotted and Large White pigs) lacking a short region of CD163 SRCR5, including the ligand-binding pocket. We generated a large number of gene-edited Large White pigs of the F0 generation for use in viral challenge studies. The results of this study show that these pigs are completely resistant to infection by species 2 PRRSV, JXA1, and MY strains. There were no clinical symptoms, pathological abnormalities, viremia, or anti-PRRSV antibodies in the CD163 SRCR5-edited pigs compared to wild-type controls after viral challenge. Porcine alveolar macrophages (PAMs) isolated from CD163 SRCR5-edited Large White pigs also displayed resistance to PRRSV in vitro. In addition, CD163 SRCR5-edited PAMs still exhibited a cytokine response to PRRSV infection, and no significant difference was observed in cytokine expression compared to wild-type PAMs. Taken together, these data suggest that CD163 SRCR5-edited pigs are resistant to PRRSV 2, providing a basis for the establishment of PRRSV-resistant pig lines for commercial application and further investigation of the essential region of SRCR5 involved in virus infection.